ĪŠONA GRADZĒS – THE EXPRESSION OF SOCIAL ASPECTS IN MASKING RITUALS IN LATGALE - Dukaļska, Iveta (Via Latgalica, 2008)
Īšona grjadzēs (gradzēs) (an expression used in Latgalian to describe a specific masking tradition) is a unique masking tradition in Latgal in the district of Ludza. It existed until the 1970s parallel to the better known čigānos iešana (literally ‘going as gypsies’). Originally, these rituals had a social meaning as an activity of the poorer classes, thereby obtaining food for the Yule festivities. Since the 1960s it has been a masking ritual performed mainly by older women. I assume that it is this particular ritual that has given rise to the mask of a beggar in a more recent masking tradition. A narrator, when asked what a gradze is, usually answers that it is a poor person, a beggar, and gradzes is a ‘group of poor people’. Groups of poor people are usually associated with filth, which is also confirmed by the looks of the gradzes through their dirty faces. In turn, one of the ritual activities of the masked groups is frightening, making noise, and attracting attention, which can be explained as a function of the frightening of evil spirits. This tradition could took place during Christmas night on December 24, whereas other groups of masked people could begin their activities only on December 25. Today, it is not possible to connect these traditions to the Catholic Church, but according to the materials of a field study which has been carried out in the region of Ludza since 2005 it is possible to conclude that īšona gradzēs was allowed by the Catholic church because this ritual was performed on the most Holy holiday night. Gradzes were considered to be the first Christmas messengers, or messengers of the birth of Christ.Until the 1960s, testimonies of the narrators and available research material relating to the masking ritual allow the conclusion that people sang the Lord’s songs when going for gradzēs, and only when asking for a treat they sang traditional Christmas songs and carols. Later, as the traditions changed, different songs were sung. Singing was accompanied by slow dancing, which mostly resembled the „standing pat”. In the 1970s, sometimes a village musician, who played harmonica or violin, would join the gradzes. Gradzes were not invited in and did not enter the rooms. The treats (sausages, pies, etc.) were offered through the windows or doors. It is possible to assume that the mythical origins of the gradzes’ image could be found in Slavic mythology, where the Slavic God Kolyada (коляда) is a child of the Sun as an image of the beginning of the new year’s cycle and festivities. In Slavic mythology, there is an image similar to the gradzes, called деды, диды, дзяды – „old men” or „greybeards”. The Ded (old man) is a guardian of the family and its children. This image was also worshiped as a giver of welfare and a master of hidden fortunes. An old man with red fiery eyes and a red beard would walk around dressed as a beggar and endow the poors he would meet. Sometimes they would say that the fortune was hidden in the old man’s dirty shredded clothes. The story goes that souls of the departed relatives would walk in the form of old men, and that these souls would be treated on a Christmas evening, taking the meals out below the window. A long-term study of the tradition of īšona grjadzēs (gradzēs) was started only in 2005. At present, the work is not yet completed and research will therefore continue to be carried on by the author of the paper.